Sustainability reporting under the EU’s new directive. Conducting a double materiality analysis - Silaskivi, Emma (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2025)
Sustainability reporting has evolved drastically, especially in recent years, moving from voluntary reporting to legal obligations. Businesses must now report on sustainability in accordance with the new EU Directive on corporate sustainability reporting (CSRD). This directive requires companies to report on their sustainability according to a double materiality perspective. However, firms face challenges in understanding what is double materiality, and which impacts, risks and opportunities regarding sustainability are relevant for them. Increasing demand for this sustainability information from various stakeholders has highlighted the growing need to understand the nature of double materiality and context of sustainability issues specific to different sectors. Currently, the foundation of sustainability reporting lies in materiality, which has evolved into a concept of double materiality under the new EU directive. Double materiality means that businesses are required to report not only on their environmental and social impacts, but also on how these impacts may affect them financially. This linkage integrates both impact and financial materiality and a holistic understanding the whole value chain in the same process. By first mapping their value chain, organisations can better understand how different issues impact various stakeholders. This approach helps identify issues the company influences as well as impacts that create either risks or opportunities for the company. The report provides insights a devised tool that can be utilized by companies to conduct a double materiality assessment. The tool considers how sector specific sustainability issues can be addressed while understanding impact of stakeholder sustainability throughout the value chain. Moreover, the study provides valuable information on the identification of relevant sustainability issues across stakeholders and company operations enabling the development of sustainability reporting and strategy.

------ Vastuullisuusraportointi on kehittynyt viime vuosina merkittävästi. Aiemmin vapaaehtoisesta raportoinnista on siirrytty lakisääteiseen raportointiin, mikä tarkoittaa, että yritysten on nyt raportoitava vastuullisuudestaan Euroopan Unionin kestävyysraportointidirektiivin mukaisesti. Tämä direktiivi vaatii yrityksiä raportoimaan sekä ympäristö- että sosiaalisista vaikutuksistaan sekä siitä, miten nämä vaikutukset voivat vaikuttaa yrityksen taloudelliseen tilanteeseen. Tätä kutsutaan kaksoisolennaisuudeksi. Monet yritykset kohtaavat haasteita ymmärtää, kuinka kaksoisolennaisuusarviointi tulisi suorittaa ja mitkä kestävään kehitykseen liittyvät vaikutukset, riskit ja mahdollisuudet ovat heille olennaisia. Sidosryhmien kasvava tarve vastuullisuustiedolle on myös korostanut tarvetta ymmärtää tätä kaksoisolennaisuuden periaatetta ja vastuullisuuskysymysten merkittävyyttä eri toimialoilla. Tällä hetkellä vastuullisuusraportointi perustuu olennaisuuteen, joka on kehittynyt uuden EU-direktiivin myötä, kun on otettu käyttöön kaksoisolennaisuuden periaate. Tämä lähestymistapa yhdistää vaikutusten ja taloudellisen olennaisuuden merkityksen koko arvoketjussa. Ensimmäinen askel on arvoketjun kartoitus, joka auttaa yrityksiä ymmärtämään paremmin, miten erilaiset tekijät vaikuttavat eri sidosryhmiin. Tämän jälkeen yritykset voivat tunnistaa ne vastuullisuusteemat, joihin niiden toiminta vaikuttaa, sekä mahdolliset taloudelliset riskit ja mahdollisuudet. Tämä raportti esittelee kehitetyn työkalun, jota yritykset voivat hyödyntää kaksoisolennaisuusanalyysin tekemisessä. Työkalussa huomioidaan toimialakohtaiset vastuullisuuskysymykset ja arvioidaan sidosryhmien vastuullisuusvaikutukset koko arvoketjussa. Tutkimus korostaa myös olennaisten vastuullisuusteemojen tunnistamisen merkitystä niin sidosryhmille kuin yritykselle itselleen. Hyvin tehty kaksoisolennaisuusarviointi voi edesauttaa vastuullisuusraportoinnin ja -strategian kehittämistä myös tulevaisuudessa.